Perluasan Pemanfaatan Surat Pernyataan Tanggung Jawab Mutlak (SPTJM) bagi Pasangan Nikah Siri dalam Mewujudkan Kepastian dan Keadilan Hukum: Expanding the Utilization of the Absolute Statement of Responsibility (SPTJM) for Couples in Unregistered Marriages to Achieve Legal Certainty and Justice - M. Kharisma Prayuda (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study aims to examine the urgency and feasibility of expanding the function of the Absolute Statement of Responsibility (SPTJM) as an initial administrative basis for couples in unregistered marriages (nikah siri) in the process of marriage validation (isbat nikah) to achieve fair and certain legal protection. This research employs a normative juridical method with statutory, conceptual, historical, and sociological approaches, using primary, secondary, and tertiary legal materials analyzed descriptively and qualitatively. The results show that expanding the function of SPTJM is in line with progressive and responsive legal theory, and has the potential to serve as a limited administrative acknowledgment without replacing official registration, yet enabling access to basic public services and acting as a preliminary step toward formal legality through the isbat nikah mechanism. This study recommends the formulation of clear technical regulations and strict supervision to ensure that SPTJM is not misinterpreted as the legalization of unregistered marriages, but is understood as a temporary solution that upholds humanitarian principles, substantive justice, and constitutional protection.